(untitled) (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Many patients with schizophrenia have severe impairments in cognitive functions, especially in memory, attention and executive functions. These impairments inevitably have an important impact on the functional outcome of the disorder. OBJECTIVE: This article focuses on aspects of cognitive function in schizophrenia, their relationship to functional outcome and the effect of antipsychotics on cognition. METHOD: Research on databases such as Medline/PubMed and Lilacs using the terms schizophrenia, cognition, neuropsychology, outcome, functioning, treatment. RESULTS: Even though a great number of studies report cognitive impairments in schizophrenia, there is no agreement in relation to the pattern of these deficits. Nevertheless, cognitive impairments have a significant correlation with functional handicaps. Second generation antipsychotics seem to have a positive impact in cognition, although the meaning of this improvement on social and functional performance of the patients is not clear. Neuropsychological rehabilitation shows discrete, though promising, results. CONCLUSION: The ability of second generation antipsychotics to improve specific domains of cognition vary as does the pattern of deficits of the patients. Thus, strategies to improve cognition in schizophrenia include the use of second generation antipsychotics associated with neuropsychological rehabilitation.